2011
DOI: 10.5032/jae.2011.02118
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Value of Volunteer Involvement

Abstract: Volunteers can be an important resource of many nonprofit organizations. The ability to meet the mission, goals and objectives of nonprofit organizations often depends upon the effectiveness of volunteer involvement in direct service delivery or indirect program support. Volunteer involvement utilizes financial and non-financial resources of an organization. Given the challenges associated with coordinating and managing volunteers, nonprofit organizations should evaluate volunteer program initiatives. Utilizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Hager and Brudney's approach -and that adopted by Terry, Harder and Pracht (2011) Addington-Hall and Karlsen (2005) found that hospice volunteers were significantly more likely than nurses to feel highly valued, to report that morale was high and that any disagreements between different groups had an insignificant impact on teamwork. Nevertheless, volunteers were significantly more likely to state that they did not receive a great deal of support from hospice staff, and nurses revealed they were unlikely to receive a great deal of support from volunteers.…”
Section: Insert Figure 1 About Herementioning
confidence: 99%
See 1 more Smart Citation
“…Hager and Brudney's approach -and that adopted by Terry, Harder and Pracht (2011) Addington-Hall and Karlsen (2005) found that hospice volunteers were significantly more likely than nurses to feel highly valued, to report that morale was high and that any disagreements between different groups had an insignificant impact on teamwork. Nevertheless, volunteers were significantly more likely to state that they did not receive a great deal of support from hospice staff, and nurses revealed they were unlikely to receive a great deal of support from volunteers.…”
Section: Insert Figure 1 About Herementioning
confidence: 99%
“…In their study, 8% were negative about their volunteer programmes (challenges outweighed benefits), 24% received a positive score (benefits outweighed challenges) between 0 and 5, 42% a score between 5 and 10, and only 26% scored above 10 (out of a maximum of 16). Terry, Harder and Pracht (2011) also utilised this approach in the US youth program 4-H, finding that services that included volunteers in a variety of roles were likely to score more highly, but that 21% of the 4-H programs scored more challenges than benefits (compared to 8% in Hager and Brudney).…”
Section: Insert Figure 1 About Herementioning
confidence: 99%
“…NFE is having similar purpose with extension education that is activities which concern on conducting outside formal institution. Based on nonprofit view, volunteer can be included as an essential foundation of many nonprofit organizations (NPO) (Terry, Harder, & Pracht, 2011). It was notified that an organization will get benefit from volunteerism since it volunteerism will saving the cost (Allen et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…According to Merriam and Cafarrella (1999), NFE is the opposite of formal learning or education which is gotten outside educational society. 4H activities for youth (Terry et al, 2011) or other youth organization such as scouting (Vaske, 2008) are several example of NFE. As aforementioned earlier, NFE cannot be separated from extension education part since both of those learning are similar that is providing social services to the community especially in education area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation